The development of tele-computer control system / Yusof Ramli - Ramli, Yusof (2000)
Today modern Telephone Network System offers a vast of communication for all the widely available telephony devices such as telephone, cellular phone, modem, fax, internet connection and a lot more. This thesis describes the development of a TeleComputer control system application and how to control remote devices, which could be anywhere in die Speech Network by utilizing the existing telephone system. The major controlling work is done via the custom developed hardware and the control software, which is written in Visual Basic (VB).